2012
DOI: 10.1115/1.4006851
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Material Microstructure Effects on the Surface Generation Process in Microendmilling of Dual-Phase Materials

Abstract: The anisotropic behavior of the material microstructure when processing multiphase materials at microscale becomes an important factor that has to be considered throughout the machining process. This is especially the case when chip-loads and machined features are comparable in size to the cutting edge radius of the tool, and also similar in scale to the grain sizes of the phases present within the material microstructure. Therefore, there is a real need for reliable models, which can be used to simulate the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Where A w is the surface area of the contact with cavity sidewalls, L is the tooth load, and r c is the tool nose radius; correspondingly, E and ν are the polymer's Young's modulus & Poisson ratio, respectively, δ represents the maximum peak to valley distance generated with the micro drill. Provided that feed rate ( f) and tool nose diameter employed during the micro drilling process are all given, the following equation (11) used to calculate the δ [106].…”
Section: Force Of Deformationmentioning
confidence: 99%
“…Where A w is the surface area of the contact with cavity sidewalls, L is the tooth load, and r c is the tool nose radius; correspondingly, E and ν are the polymer's Young's modulus & Poisson ratio, respectively, δ represents the maximum peak to valley distance generated with the micro drill. Provided that feed rate ( f) and tool nose diameter employed during the micro drilling process are all given, the following equation (11) used to calculate the δ [106].…”
Section: Force Of Deformationmentioning
confidence: 99%
“…This will lead to further development of the micro-milling process as a whole and offer insights into better microstructure design when micro-milling. With regard to surface roughness, Elkaseer et al [ 136 ] presented a model to simulate the surface generation process in micro-milling of multiphase materials. They confirmed that their developed model could be used to predict the surface quality after machining under various machining parameters and could further be used to optimize the process for multiphase materials.…”
Section: Process Inputsmentioning
confidence: 99%
“…Given that the feed rate, f , spindle speed, V, and tool nose radius used during the micro drilling process are known parameters, it is possible to calculate δ as follows (Elkaseer et al 2012):…”
Section: Deformation Forcementioning
confidence: 99%